POSITIVES AND NEGATIVES OF IVANA DOBRAKOVOVA'S PROSE MATKY A KAMIONISTI - Fedorková, Andrea (Bohemica Olomucensia, 2020)
The paper deals with the last Ivana Dobrakovova's prose Matky a kamionisti (2018). At first we analyse specific poetological aspects of her writing. We focuse on modeling of protagonists in five proses ("Otec", "Ivana", "Olivia", "Lara" and "Veronika"), predominantly on relationship between main character and her father, motives of body and sexuality and symptoms of mentally sick heroines. With help of interdisciplinary knowledge from psychiatry it is possible to establish accurate, medical diagnoses of literary characters. This approach offers a more detailed analyse of Dobrakovova's proses and new perspective of interpretation of her texts.
Keywords: literary criticism; Ivana Dobrakovová; interdisciplinary research